Restoring the threatened Scalesia forest: insights from a decade of invasive plant management in Galapagos - Jäger, Heinke; San-José, Miriam; Peabody, Clare; Chango, Rafael; Sevilla, Christian (Frontiers in Forests and Global Change, 2024)
Island forests are becoming increasingly fragmented and colonized by invasive species, which can eventually lead to local species extinctions. In the Galapagos Islands, invasive species pose a serious extinction threat to the endemic daisy tree Scalesia pedunculata, formerly the dominant habitat-forming species of the unique Scalesia forest. This forest has been reduced to fragments due to land use changes in the past and is now increasingly invaded by introduced plants. We conducted a field experiment on Santa Cruz Island to assess the impacts of blackberry (Rubus niveus) and two other invasive plant species, Cestrum auriculatum and Tradescantia fluminensis, as well as the effects of the removal of two of these (R. niveus and C. auriculatum) on cover, composition and diversity of the resident plant communities. Particular attention was paid to effects of the invasive species on the S. pedunculata population. Annual vegetation monitoring was carried out in a total of 34 permanent plots (10 m × 10 m) over 10 years (2014–2023), using the line-intercept method. Seventeen of these plots were established in an invaded area and 17 plots in an area with continuous invasive plant removal since 2014. Results indicated that there were significant changes in both the species composition of the plant communities and average percent cover of species over time, comparing removal plots with invaded plots. Species composition in removal plots changed significantly more than in invaded plots, towards a plant community with greater percent cover of endemic species. A significant negative relationship between the three invasive species and cover of S. pedunculata suggested that multiple invader species may have additive negative impacts. Natural recruitment of S. pedunculata by seeds was observed in the removal but not in the invaded plots. These results, as well as the striking decrease of 71% in cover of adult S. pedunculata in the invaded plots indicate that this threatened species will be driven to local extinction on Santa Cruz Island, Galapagos, in less than 20 years if invasive plant species are not removed on a large scale.